Inclusive leadership and subordinates’ career calling: roles of belongingness and organization-based self-esteem - Ma, Guangya; Wang, Longmei; Sun, Siwei; Lu, Lei (Frontiers in Psychology, 2025)
IntroductionWhile the concept of career calling has garnered attention for its role in inspiring employees’ sense of purpose and engagement, the literature on its developmental aspects, especially the influence of leadership styles, has not been fully paid attention to. Furthermore, the association between leadership styles and career calling still needs further exploration. Therefore, this study narrows this gap through testing the mediating role of belongingness in the relationship between inclusive leadership and career calling and its variation across different levels of organization-based self-esteem. Drawing upon the Need-to-Belong Theory, we propose a moderated mediation framework to elucidate the relationship and its variations between inclusive leadership and career calling among employees.MethodsData was collected from 337 employees across various industries in Guangdong, Zhejiang, and Beijing, China, using a two-wave lagged questionnaire. We used Inclusive Leadership-9, Belongingness-12, Organization-Based Self-Esteem-10 and Career Calling-12 measurement variables. Later, we used SPSS and PROCESS to verify five hypotheses.ResultsStatistical testing revealed that (1) there is a positive relationship between inclusive leadership and career calling. (2) Belongingness plays a mediating role in the relationship between inclusive leadership and career calling. (3) Organization-based self-esteem moderates the association between inclusive leadership and career calling, both directly and indirectly through belongingness.ConclusionThis study provides insights into the conversation about inclusive leadership and career calling, revealing a deeper understanding of the associations between leadership styles and employees’ vocational fulfillment, and suggesting practical implications for encouraging an inclusive work environment that supports career development.